(untitled) (Research, Society and Development, 2020)
Objective: Evaluate the severity of tuberculosis and its association with laboratory tests before antituberculosis treatment. Methodology: Patients with pulmonary tuberculosis were evaluated for severity using data available in medical records (Clinical; Excretion of mycobacteria; and Diagnostic imaging) and associated with biochemical and hematological parameters requested at the time of diagnosis and before antituberculosis treatment. Results: The evaluation of the severity showed a predominance of smear AFB (+), fever associated with other symptoms and infiltrative tuberculosis. Only a positive correlation between mycobacteria excretion and imaging diagnosis (rho=0.47; p=0.023) was observed. The patients presented hyponatremia (9/21), hypomagnesemia (6/13), and hypercalcemia (1/13), unrelated to the severity. The presence of fever influenced the number of non-segmented neutrophils (p=0.0142) and the total leukocyte count correlated with the increase in total neutrophils (rho=0.9631; p<0.0001). Conclusion: Different severity characteristics of tuberculosis, although they reflect the degree of commitment of the patient, are not always correlated; the evaluation of electrolytes could contribute to clinical behavior; and non-segmented neutrophils are associated with a worse clinical prognosis in patients with tuberculosis.